2011
DOI: 10.4049/jimmunol.1002680
|View full text |Cite
|
Sign up to set email alerts
|

NTPDase1 Controls IL-8 Production by Human Neutrophils

Abstract: The ectonucleotidase NTPDase1 (CD39) terminates P2 receptor activation by the hydrolysis of extracellular nucleotides (i.e., the P2 receptor ligands). In agreement with that role, exacerbated inflammation has been observed in NTPDase1-deficient mice. In this study, we extend these observations by showing that inhibition of NTPDase1 markedly increases IL-8 production by TLR-stimulated human neutrophils. First, immunolabeling of human blood neutrophils and neutrophil-like HL60 cells displayed the expression of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 54 publications
1
46
0
1
Order By: Relevance
“…Interestingly, Lavoie et al (26) demonstrated localization of a family of membrane-bound ectonucleotidases, the nucleoside triphosphate diphosphohydrolases (NTPDases), to the epithelium of the foregut, as well as the entire enteric nervous system. Kukulski et al (23) showed that one member of this family of ectonucleotidases, NTPDase1, controls IL-8 production by human neutrophils through regulation of P2Y receptor activation, demonstrating a clear relationship between dephosphorylation of luminal nucleotides and intestinal inflammation. The NTPDase family of enzymes has a similar function of hydrolysis of nucleotides, as we have demonstrated in the case of IAP, a secreted enzyme that maintains activity throughout the entire small intestine and colon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Lavoie et al (26) demonstrated localization of a family of membrane-bound ectonucleotidases, the nucleoside triphosphate diphosphohydrolases (NTPDases), to the epithelium of the foregut, as well as the entire enteric nervous system. Kukulski et al (23) showed that one member of this family of ectonucleotidases, NTPDase1, controls IL-8 production by human neutrophils through regulation of P2Y receptor activation, demonstrating a clear relationship between dephosphorylation of luminal nucleotides and intestinal inflammation. The NTPDase family of enzymes has a similar function of hydrolysis of nucleotides, as we have demonstrated in the case of IAP, a secreted enzyme that maintains activity throughout the entire small intestine and colon.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were maintained in a specific pathogen-free environment at MGH in accordance with the guidelines of the Committee on Animals of Harvard Medical School. All experiments were reviewed and approved by the Institutional Animal Care and Use Committee and carried out according to regulations of the Subcommittee on Research Animal Care of the MGH and the National Institutes of Health (NIH Publication 85- 23,1985).…”
Section: Methodsmentioning
confidence: 99%
“…5 ATP is involved in chemotaxis 47,48 and can activate neutrophils [48][49][50] and monocytes. 47,51,52 Also here, at the level of the inflammatory system, adenosine seems to counteract the effects of ATP because adenosine suppresses neutrophil and monocyte-macrophage activation and recruitment in vivo and vitro.…”
Section: Effects Of Atp and Adenosine On The Immune Responsementioning
confidence: 99%
“…The same researchers translated their findings into an in vivo model showing A3 and P2Y2 receptors to control the recruitment of neutrophils to the lung in a mouse model of sepsis [35,56]. The involvement [10,19,191,192] Chemotaxis P2Y 2 [141,193] Release of chemokines and cytokines P2Y 2 , P2X1, P2X7, and P2Y 6 [196,197] Ambiguous data reporting the ATP to be a long-range chemoattractant without phagocytic activity [115] vs. ATP as an autocrine/paracrine signal limited to influence chemotaxis but accompanied with phagocytosis by locally inducing lamellipodial membrane extensions [117,118] of the neutrophilic P2Y 2 receptor in neutrophil migration was corroborated by several other research papers by the group of Sévigny who described that P2Y 2 receptor activation on neutrophils is required for IL-8 (released from monocytes/macrophages and/or epithelial cells at sites of inflammation) to induce most efficient neutrophil chemotaxis [57], and that P2Y 2 receptors on neutrophils are implicated in the potentiation of IL-8 production by human neutrophils themselves, a mechanism under tight control by the ectonucleotidase "Ecto-nucleoside triphosphate diphosphohydrolase 1" (E-NTPDase1 or CD39) expressed on the surface of neutrophils [58]. E-NTPDase1 also regulates the migration speed of neutrophils but not their ability to detect the orientation of the gradient field generated by fMLP that induces an autocrine ATP release via stimulation of the formyl peptide receptor [59].…”
Section: Introductionmentioning
confidence: 99%